(untitled) (Journal of the College of Basic Education, 2023)
Iraq witnessed a structural imbalance in the joints of public life and art in particular. The deep winds that afflict peoples and the winds of change are in the form, because what happened was a fundamental change both in terms of content and format. This approach ascended to the stage, and the expression of this was crystallized in the examination of texts. life and social aspects and stand on some of its secondary features behind the forms and behavior, and in this sense The Iraqi theater has found in the episodes of life what can be read and manifested in the theatre.